2019
DOI: 10.1128/jcm.00319-19
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Antimicrobial Resistance, and Public Health Insights into Enterococcus spp. from Australian Chickens

Abstract: Due to Australia’s management of antimicrobial use in poultry, particularly the discontinued use of avoparcin for nearly 20 years, it is hypothesized that vancomycin-resistant enterococci associated with human disease are not derived from poultry isolates. This study evaluated antimicrobial resistance (AMR) of five enterococcal species isolated from Australian meat chickens, genomic features of Enterococcus faecium and Enterococcus faecalis, and the phylogenetic relationship of the poultry-derived E. faecium w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 58 publications
3
22
0
Order By: Relevance
“…E. faecium in pigs did not harbor the vanA or vanB operons, which are commonly found in the major hospital-adapted strains. As hypothesized in a recent study by O'Dea et al, it appears that the genetic makeup of this subset of enterococci found in chickens, humans, and now pigs does not favor the uptake of vanA or vanB operon-containing genetic elements (22). Moreover, MLST, PCA, and SNPbased phylogenetic analysis indicate some similarities within the populations of E. faecium in pigs and humans.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…E. faecium in pigs did not harbor the vanA or vanB operons, which are commonly found in the major hospital-adapted strains. As hypothesized in a recent study by O'Dea et al, it appears that the genetic makeup of this subset of enterococci found in chickens, humans, and now pigs does not favor the uptake of vanA or vanB operon-containing genetic elements (22). Moreover, MLST, PCA, and SNPbased phylogenetic analysis indicate some similarities within the populations of E. faecium in pigs and humans.…”
Section: Discussionmentioning
confidence: 71%
“…A recent study performed on enterococci from Australian meat chickens found clinical resistance to a number of antimicrobials. The study, however, did not identify any resistance to vancomycin (22), providing evidence of success in antimicrobial stewardship measures. Moreover, E. faecium from meat chickens was found to be genetically distinct from hospital-adapted strains.…”
mentioning
confidence: 74%
“…The value of resistance to vancomycin in E. faecalis found in laying hens was higher than in other animal productions and should be further investigated, as this could represent a source of AMR to this antibiotic. The highest percentage of resistance obtained was for quinupristin-dalfopristin (93.33%), which was expected considering that E. faecalis are intrinsically resistant to this antibiotic [ 44 ]. This antibiotic is very important in hospital intensive care units to treat vancomycin-resistant E. faecium infections [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 85%
“…This means that animal bacteria may become resistant under selective pressure; then, bacteria travel from farms to stores, and then they may cause hard-to-treat infections in the final consumer as a consequence [ 48 , 49 , 50 , 51 ]. The relationship between massive use of antibiotics to treat or prevent illnesses or for growth purposes and the consequent emergence of several AMR mechanisms in food animals followed by spread into the environment has been clearly highlighted in several reports [ 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ]. Very recently, the first cases of linezolid-resistant coagulase-negative staphylococci recovered in healthy turkeys in Egypt have been reported, as did the massive use of antibiotics in African countries in food-producing animals [ 62 , 63 ].…”
Section: Amr In Animalsmentioning
confidence: 99%